Representasi Nilai-Nilai Keislaman DALAM FILM “CHILDREN OF HEAVEN” DAN RELEVANSINYA DENGAN PENDIDIKAN KARAKTER - Wiwiek Afifah (Mukaddimah: Jurnal Studi Islam, 2018)
This study aims to: (1) describe the Islamic values in film “Children of Heaven” and (2) determine its relevance to character education. The research design is an inferential content analysis. The entirely data are derived from the film “Children of Heaven” while its research instrument is the human instrument. The data obtained from recording the Islamic values found in the film then and the data procurement measures include: (1) the determination of the examples Islamic values contained in the film, (2) recording, and (3) determination of the units. Data validation was done by means of doing discussion to those findings to some experts and peers. Data analysis technique used in the research is to classify, interpret, and conclude. The results showed that; (1) Islamic values consist of two categories: (a) Islamic values associated with character education of children in the family such as patience, mutual help, humility, simplicity, birul walidain (devoted to parents), sincerity, mutual affection-love, qonaah (grateful), not easy to despair, and compliance in religion, whereas (b) Islamic values associated with formal education (school) is the spirit of being a hard student, self-discipline, independent, honest, and an ability in getting the problem solving. (2) There is a great relevance between the values contained in the film “Children of Heaven” to the character education such as religious value, honest, discipline, well-motivated students, loyal, independent, and enable to set the problem solving.